Block Split Subdivision Domination in Graphs - Muddebihal, M. H.; Shekanna, P; Ahmed, S. (Journal of Scientific Research, 2015)
A dominating set D ? V[BS(G)] is a split dominating set in [BS(G)] if the induced subgraph ?V[BS(G)] - D? is disconnected in [BS(G)]. The split domination number of [BS(G)] is denoted by ?sbs(G), is the minimum cardinality of a split dominating set in [BS(G)]. In this paper, some results on ?sbs(G) were obtained interms of vertices, blocks and other different parameters of G but not the members of [BS(G)]. Further we develop its relationship with other different domination parameters of G.